Tehnična in estetska življenjska doba lesa - Humar, Miha (Acta silvae et ligni, 2020)
In outdoor applications wood is exposed to biotic and abiotic degradation factors. These processes are essential for carbon circulation. However, if wood is used in commercial applications, these processes need to be slowed down as much as possible. When wood is degraded, it has to be replaced. In general, wooden elements are replaced for aesthetic reasons or due to the failure to meet technical requirements. This paper describes the most important mechanisms of wood degradation in outdoor applications. Special emphasis is given to the natural durability of wood and state-of-the-art preservation solutions. In addition, key results on the performance of the wooden on the decking of a study object in Ljubljana are presented. The decking represents a similar exposure to that of bridges, outdoor flooring or roofs, and therefore can be used as a model for the assessment of the performance of wood used outdoors.
Keywords: barvne spremembe; colour changes; decay; durability; les; lesne glive; odpornost lesa; razkroj; service life; wood; wood inhabiting fungi; življenjska doba lesa